2021
DOI: 10.1093/ptj/pzab117
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Sedentary Behavior as Experienced by People in the Transition From Working Life to Retirement: An Empirical Phenomenological Study

Abstract: Objective Sedentary behavior (SB) is defined as a mean of >6 hours of daytime sitting or lying down. SB has been shown to increase with older age and is a risk factor for disease. During the transition from working life to retirement, changes in daily life activities occur, risking increased SB. The aim of the present study was to gain a deeper understanding of SB in relation to the transition from working life to retirement as experienced by persons in retirement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This finding is concerning because PA in older age decreases the risk of several lifestyle-related diseases and comorbidity [ 51 ], while the number of sedentary hours is found to be associated with an increased risk of mortality [ 52 ]. The oldest age group had the lowest number of sedentary hours, which is surprising because sedentary time usually increases during retirement and old age [ 53 ] and is described as a natural aspect of aging [ 54 ]. Notably, the youngest age group in this study reported a high level of sedentary time during the pandemic and they experienced a greater decrease in their total PA levels compared with the adult group.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concerning because PA in older age decreases the risk of several lifestyle-related diseases and comorbidity [ 51 ], while the number of sedentary hours is found to be associated with an increased risk of mortality [ 52 ]. The oldest age group had the lowest number of sedentary hours, which is surprising because sedentary time usually increases during retirement and old age [ 53 ] and is described as a natural aspect of aging [ 54 ]. Notably, the youngest age group in this study reported a high level of sedentary time during the pandemic and they experienced a greater decrease in their total PA levels compared with the adult group.…”
Section: Discussionmentioning
confidence: 99%
“…Participants found options such as watching television easier to engage in. Participants within the study identified SB similarly to those in the Sweden (Eklund et al, 2021). SB was identified as unhealthy compared to PA and led to poor health.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy a longitudinal study examined the experience of PA across retirement in a three year-long study (Socci et al, 2021). Using a phenomenological approach, another study looked into the meaning attached to SB during the retirement transition (Eklund et al, 2021). As older adults are a heterogenous group, these studies identified the need to further research the meaning people attach to PA and SB when going through the retirement transition.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies were identified that looked at the participants’ perceptions of retirement on SB [ 17 , 18 ]. Van Dyck et al [ 17 ] found that participants felt that retirement influenced their SB.…”
Section: Introductionmentioning
confidence: 99%
“…They experienced a decrease in sitting time during transport and engaged in active transportation. Eklund et al [ 18 ] identified two themes on how retirement influences SB: (1) the theme ‘in light of meaningful SB’, related to the meaning of sedentary activities, in which participants viewed SB as a possibility to perform activities that they were unable to when still in employment; (2) the theme ‘in the shadow of involuntary SB’, which was about the unhealthy aspect of SB and factors that contributed towards the development of such behaviour.…”
Section: Introductionmentioning
confidence: 99%